Less-Affected Hand Function Is Associated With Independence in Daily Living: A Longitudinal Study Poststroke. Issue 3 (March 2022) - Hmaied Assadi, Samar; Barel, Haim; Dudkiewicz, Israel; Gross-Nevo, Revital Feige; Rand, Debbie
Abstract : Background and Purpose: The upper extremity (UE) ipsilateral to the brain lesion is mildly affected poststroke. It is unclear whether patients perceive this, and the association between less-affected hand function and independence in activities of daily living (ADL) is unknown. We aimed to (1) assess longitudinal changes in function, dexterity, grip strength, and self-perception of the less-affected UE, (2) compare them to the normative data, and (3) determine the association of both UEs to ADL during the first 6 months poststroke. Methods: Consecutive adults following a first stroke were assessed on rehabilitation admission (T1), 6 weeks (T2), and 6 months (T3) poststroke onset. Box and block test assessed function of both UEs. The functional dexterity test (FDT) and Jamar Dynamometer assessed dexterity and grip strength of the less-affected UE. The functional independence measure assessed ADL, and instrumental ADL was assessed at T3. Spearman correlations and multiple regression models were used. Results: Participants were assessed at T1 (N=87), T2 (N=82), and T3 (N=68). At T1, less-affected UE deficits were apparent (median [interquartile range] box and block test-45 [35–53] blocks, FDT-44.5 [33.3–60.8] seconds, grip-25.5 [16.2–33.9] kilograms), but only 19.5% of the participants self-perceived this. Less-affected hand function significantly improved with 32% and 33% achieving a minimal clinically important difference for box and block test at T2 and T3, respectively. Dexterity improved significantly between T1 and T2 ( P <0.001, no established minimal clinically important difference) and grip strength improved significantly between T2 and T3; 3.4% achieving a minimal clinically important difference ( P <0.01). At T3, most participants did not reach the norms (box and block test-67.4 blocks, FDT-32.2 seconds, grip-40.5 kilograms). Both the less- and more-affected UEs explained a large portion of the variance of ADL at all time-points, after controlling for age, days-since-stroke-onset, stroke type, and cognition. Conclusions: Despite some improvement, the less-affected UE at 6 months poststroke remained below norms, explaining difficulties in ADL and instrumental ADL. Further research is needed. Abstract : Supplemental Digital Content is available in the text.